Reception and reaction to French Enlightenment and Revolution in late colonial/early independent Spanish America: New Granada, Peru and Venezuela 1790-1812 - Wallace, Richard James (2008)
This dissertation explores the reception of French Enlightenment thought and the reaction to French revolutionary events in late colonial and early independent Spanish America between 1790 and 1812, focusing on New Granada, Peru and Venezuela. The years leading up to the historical and political processes known as Spanish American Independence witnessed radical transformations; during this period accepted wisdom was questioned, new discoveries were made and questions of political rights were open to debate. This dissertation, through a close reading of the contemporary periodical press and early discourses of Simon Bolivar, assesses the dissemination of the French Enlightenment and news of the 'Age of Revolution' in colonial society. The initial rejection of Revolutionary events is examined in the Papel Periodico de Bogota, whilst the Mercurio Peruano charts scientific discovery through the 1790s. Following the Napoleonic invasion of the Iberian peninsula, 1808, the Gazeta de Caracas is studied to demonstrate the change in attitudes and cautious desire for autonomy. Finally, the early writings of Simon Bolivar are used to assess the compatibility and appropriation of Enlightenment thought and revolutionary models within colonial society. It will be shown that a public sphere did exist amongst a small, but highly educated, colonial elite in the 1790s, and that French Enlightenment ideas had been transmitted to Spanish America and were in circulation. However, the arrival of the Enlightenment and news of Revolution in the Spanish colonies was partial and fragmented; some parts were strongly rejected whilst others were embraced. A detailed, logical development is recorded in the periodical press. Following the events of 1808, heightened Creole discontent and the acceptance of the principles of 1789 are shown to propel the Independence movement forward.